Uridine Adenosine Tetraphosphate-Induced Coronary Relaxation Is Blunted in Swine With Pressure Overload: A Role for Vasoconstrictor Prostanoids - Zhou, Zhichao; Lankhuizen, Inge M.; van Beusekom, Heleen M.; Cheng, Caroline; Duncker, Dirk J.; Merkus, Daphne (Frontiers in Pharmacology, 2018)
Plasma levels of the vasoactive substance uridine adenosine tetraphosphate (Up4A) are elevated in hypertensive patients and Up4A-induced vascular contraction is exacerbated in various arteries isolated from hypertensive animals, suggesting a potential role of Up4A in development of hypertension. We previously demonstrated that Up4A produced potent and partially endothelium-dependent relaxation in porcine coronary microvasculature. Since pressure-overload is accompanied by structural abnormalities in the coronary microvasculature as well as by endothelial dysfunction, we hypothesized that pressure-overload blunts the coronary vasodilator response to Up4A, and that the involvement of purinergic receptors and endothelium-derived factors is altered. The effects of Up4A were investigated using wire-myography in isolated coronary small arteries from Sham-operated swine and swine with prolonged (8 weeks) pressure overload of the left ventricle induced by aortic banding (AoB). Expression of purinergic receptors and endothelium-derived factors was assessed in isolated coronary small arteries using real-time PCR. Up4A (10-9-10-5 M) failed to produce contraction in isolated coronary small arteries from either Sham or AoB swine, but produced relaxation in preconstricted arteries, which was significantly blunted in AoB compared to Sham. Blockade of purinergic P1, and P2 receptors attenuated Up4A-induced coronary relaxation more, while the effect of P2X1-blockade was similar and the effects of A2A- and P2Y1–blockade were reduced in AoB as compared to Sham. mRNA expression of neither A1, A2, A3, nor P2X1, P2X7, P2Y1 P2Y2 or P2Y6-receptors was altered in AoB as compared to Sham while P2Y12 expression was higher in AoB. eNOS inhibition attenuated Up4A-induced coronary relaxation in both Sham and AoB. Additional blockade of cyclooxygenase enhanced Up4A-induced coronary relaxation in AoB but not Sham swine, suggesting the involvement of vasoconstrictor prostanoids. In endothelium-denuded coronary small arteries from normal swine, thromboxane synthase (TxS) inhibition enhanced relaxation to Up4A compared to endothelium-intact arteries, to a similar extent as P2Y12 inhibition, while the combination inhibition of P2Y12 and TxS had no additional effect. In conclusion, Up4A-induced coronary relaxation is blunted in swine with AoB, which appears to be due to the production of a vasoconstrictor prostanoid, likely thromboxane A2.